Dialogic Reading and Promoting the Components of Reading Literacy in Pre-school (Preučevanje otroške in mladinske književnosti, 2025)
This article presents a variety of reading materials on nutrition in pre-school that allow for cross-curricular integration and promote the development of the components of reading literacy. Reading literacy is a lifelong process that can be fostered by objectives and content of all curricular areas of activity in the pre-school through a variety of didactic approaches, among which the dialogic reading can be very effective in the process of learning, extending and deepening of knowledge, thanks to the option of returning to the reading material several times. For the case study involving third-year students of Early Childhood Education Studies (n = 16), we chose the work by Vesna Radovanovič and Nataša Vertelj, Potato Ice Cream. The analysis of the responses presents some possibilities for cross-curricular integration and contributes to the development of the components of reading literacy.